Managerial Guidelines for Leadership Development of Administrators in Secondary Vocational Schools under Guangzhou Province - Yuting, Rao; Viphoouparakhot, Vorachai; Jirarotephinyo, Nitwadee (APHEIT International Journal of Interdisciplinary Social Sciences and Technology, 2023)
The purpose of this research was to propose managerial guidelines for leadership development of administrators in Secondary Vocational Schools under Guangzhou Province, the People’s Republic of China. The research used a mixed methods design including quantitative and qualitative research. The key informants for in-depth interview were 19 administrators from secondary vocational schools in Guangzhou, obtained through a purposive sampling method, which were analyzed by content analysis and key informants for focus group discussion were 11 experts to verify managerial guidelines. The research findings proposed the managerial guidelines for leadership development of administrators in Secondary Vocational Schools under Guangzhou Province including: (1) Principals should improve their personal quality, enhance their professionalism, improve their moral cultivation, enhance their personal charisma, recognize their role, change their leadership concept and innovate their school philosophy; (2) Schools should improve their school hardware and software, enhance teachers’ welfare, strengthen their organizational culture and innovate their school management model; (3) Education administration departments should create a good social atmosphere, improve the social status of secondary vocational school headmasters, improve the management system of headmasters, stimulate their intrinsic motivation, improve the training system of headmasters, and improve the quality of headmaster training.